2005
DOI: 10.17705/1cais.01629
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Graduating MIS Students Starting Salary in Boom and Bust Job Markets

Abstract: This study investigates the influence of internship experience, grade-point average (GPA), and job market on the starting salaries of management information systems (MIS) graduates. The seven-year period of the study includes the strong job market of the Internet boom, as well as the weak job market following the Internet bust. The regression results indicate that several factors are significantly related to starting salary including internship experience, GPA, job market, and size of employer. Internship expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…Based on the correlation analysis of this study, we can conclude that there is no statistical evidence that the first salary of PR program graduates is associated with GPA and wait time before finding a job. It is an exciting finding, as past studies have shown an association between GPA and income (Sandvig et al, 2005;Harrell et al, 1977;Saksilowati, 2007), which is not found in this study.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…Based on the correlation analysis of this study, we can conclude that there is no statistical evidence that the first salary of PR program graduates is associated with GPA and wait time before finding a job. It is an exciting finding, as past studies have shown an association between GPA and income (Sandvig et al, 2005;Harrell et al, 1977;Saksilowati, 2007), which is not found in this study.…”
Section: Resultscontrasting
confidence: 48%
“…A study that predicted the compensation of MBA graduates by accounting for their personality, age at graduation, business aptitude, and GPA showed that GPA is a significant predictor of earnings (Harrell et al, 1977). Regression analysis of management information system graduates showed the association between starting salary, internship experience, GPA, job market, and employer size (Sandvig et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging internships is one way to promote industry knowledge and experience. One study [Sandvig et al, 2005] showed that internship experience is the single most influential factor for predicting starting salary for IS graduates, much more important than either GPA or the strength of the job market. The study found that internship experience is particularly important during weak job markets.…”
Section: Internship Examplarmentioning
confidence: 99%
“…Along those lines, many scholars in the IS community have identified and described a crisis in the field. Several papers have offered explanations for the crisis [e.g., Benbasat and Zmud 1999;Davenport 1999;Markus 1999;Watson et al 2000;Alter 2003;Hirschheim and Klein 2003;DeSanctis 2003;Sandvig et al 2005;Hirschheim 2006;Neufeld et al 2007].…”
Section: Drivers Of the Crisis In The Is Fieldmentioning
confidence: 99%
“…of offshoring agreements needed to be incorporated in the IS curriculum in addition to strengthening the understanding of contemporary technologies and assessing their application suitability in specific business process contexts. Systems [e.g., DeSanctis 2003;Galliers 2003;Davis et al 2006;Hirschheim 2006] and in the Communications of the Association for Information Systems [e.g., Lucas 1999;Watson et al 2000;Ives et al 2002;Alter 2003;George et al 2005;Markus 2005;Sandvig et al 2005;Abraham et al 2006;Cederlung et al 2007;Looney and Akbulut 2007;Neufeld et al 2007]. The AIS should encourage its members to offer further educational articles about IS content.…”
Section: Academic Is Associations and Schoolsmentioning
confidence: 99%